THE CONCEPTUAL FRAMEWORK OF THE INTENTION ON ISLAMIC ESTATE PLANNING PRACTICE AMONG MUSLIM ENTREPRENEURS - Nurul Nazlia Jamil; Noradilah Abdul Hadi; Nur Shuhada Kamarudin; Azreen Jihan Mohd Hashim (Journal of Islamic, Social, Economics and Development, 2019)
Islamic estate planning is the last process of Islamic personal financial planning which is very crucial. In the Islamic point of view, there is specific focus on the rules of estate planning for instance Faraid law. In addition, there are also several other estate planning’s instruments offered in the Malaysian market such as Hibah and Wassiyah. However, most of the literature previously found that Malaysian are lack of awareness on Islamic estate planning. Considering the potential amount of wealth owned, therefore, this study will investigate the effect of factors namely attitude, subjective norms, perceived behavioural control and Islamic estate planning knowledge towards the intention of Islamic estate planning behaviour specifically among Muslim entrepreneurs. The implications of this study are pertinent to several parties such as financial planners, practitioners, and financial institutions; provides a useful insight into the personal financial planning studies.